PERBAIKAN KUALITAS LAYANAN PENDIDIKAN DI JURUSAN TEKNIK GRAFIKA DAN PENERBITAN POLITEKNIK NEGERI JAKARTA DALAM MEMENUHI HARAPAN MAHASISWA - Saeful Imam (Operations Excellence: Journal of Applied Industrial Engineering, 2015)
Abstract. Bearing the title of public universities do not make the Department ofGraphic and Publishing - PNJ can relax in getting prospective students , this canbe seen from the decrease in the number of students who follow the specializationin the admission of students from year to year. The Department needs to do propermarketing efforts . One form of marketing that can be done is the Word of Mouth(WOM) marketing. Word of Mouth Marketing, can only be achieved if studentsare satisfied with the services provided. The results of the satisfactionmeasurement using SERVQUAL method, students are not satisfied with theservice and the value of the gap all the negative attributes, while basedmeasurements with IPA and QFD obtained five priority improvement is toprovide a suggestion box for students and accommodate the needs/complaints ofstudents through the PA (academic supervisor), makes excellent service standardsfor each division there, strengthen and expand the internet network and theexisting intercom especially classrooms, complete the number of books, the layoutof the book and reading room and create an e-library system to facilitate thesearch, borrow and return books, make plans for the procurement of laboratoryand workshop equipment .Keywords: education, SERVQUAL, IPA, QFD